Advanced Management Accounting - Kaplan, Robert S. (New Delhi, India : Prentice-Hall, 1988)
The purpose of this book is to teach students how to apply analytic reasoning and use formal models when designing and evaluating management accounting systems.
includes index
jbi, 21/03/2018
Loan
Keywords: Accounting